2018
DOI: 10.1186/s12885-018-4936-y
|View full text |Cite
|
Sign up to set email alerts
|

Caveolin-1 expression predicts efficacy of weekly nab-paclitaxel plus gemcitabine for metastatic breast cancer in the phase II clinical trial

Abstract: BackgroundNanoparticle albumin-bound (nab)-paclitaxel has better efficacy, safety profiles, and no need to use prophylactic steroids compared with solvent-based paclitaxel. We performed a single arm, phase II study to evaluate the efficacy and safety of weekly nab-paclitaxel and gemcitabine combination in patients with metastatic breast cancer (MBC) and explored role of tumor/stromal Caveolin-1 (Cav-1) as a predictive biomarker for the efficacy.MethodsNab-paclitaxel (125 mg/m2) and gemcitabine (800 mg/m2) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 21 publications
1
21
0
Order By: Relevance
“…Because this regimen has toxicity but only limited activity, identification of predictive biomarkers would be quite helpful for patient selection. Previous studies suggested that expression of either SPARC or CAV‐1 in archival tumor samples may correlate with response to nab‐paclitaxel, 20‐22 which fits with the presumed method of drug entry into the tumor cell. However, not all studies confirm this association between SPARC expression and response to nab‐paclitaxel, 32 and it is possible that the predictive value of the marker may depend on tumor type or expression in stroma versus tumor cells 33 .…”
Section: Discussionmentioning
confidence: 77%
See 2 more Smart Citations
“…Because this regimen has toxicity but only limited activity, identification of predictive biomarkers would be quite helpful for patient selection. Previous studies suggested that expression of either SPARC or CAV‐1 in archival tumor samples may correlate with response to nab‐paclitaxel, 20‐22 which fits with the presumed method of drug entry into the tumor cell. However, not all studies confirm this association between SPARC expression and response to nab‐paclitaxel, 32 and it is possible that the predictive value of the marker may depend on tumor type or expression in stroma versus tumor cells 33 .…”
Section: Discussionmentioning
confidence: 77%
“…Based on the mechanism of nab-paclitaxel cell entry, protein expression of CAV-1 and SPARC are putative biomarkers for activity of this drug. [20][21][22] Similarly, human equilibrative nucleoside transporter-1…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Cav-1 is the main component of plasma membrane invaginations (calveolae), and deregulation of tumor Cav-1 is highly implicated in BC. Moreover, loss of stromal Cav-1 plays an important role in disease recurrence and overall worse prognosis of BC patients [137]. Due to the presence of albumin, the binding of nab-PTX to gp60, an albumin receptor on endothelial cells, leads to the activation of caveolin-1 (Cav-1) and formation of calveolae [135].…”
Section: Albumin-bound Paclitaxel and Comparison With Its Conventionamentioning
confidence: 99%
“…Most of these studies have been conducted in patients with breast and lung cancer, treatments which involve chemotherapy drugs that have to be internalized to be active. For breast cancer, nab-paclitaxel have been associated with highest intracellular concentration and activity whenever higher levels of Cav-1 expression were observed [ 24 , 25 ]. In particular, in metastatic breast cancer, Ricci et al evidenced that higher tumor and lower stromal Cav-1 levels were significantly correlated with a longer PFS of nab-paclitaxel and gemcitabine [ 26 ].…”
Section: Discussionmentioning
confidence: 99%